The Impact of Strategic Thinking on Risk Management: The Moderating Role of Organizational Support at Omani Construction Companies - Hamood Alhasani, Abdullah; Jaralla Alkshali , Shaker (Jordan Journal of Business Administration, 2024)
The aim of this study is to measure the impact of strategic thinking dimensions (strategic intent, systemic perception, deriving hypotheses, thinking in time and seizing opportunities) on risk management dimensions (risk identification, risk assessment, risk response and risk control) at Omani contracting companies. The study also aims to clarify the moderating role of organizational support in improving the impact of strategic thinking on risk management for these companies. The study population consisted of (205) Omani contracting companies. The comprehensive survey method was adopted, where (205) questionnaires were distributed, with (149) questionnaires valid for statistical analysis being retrieved. The study adopted the quantitative descriptive approach. Regression coefficient and hierarchical regression were used among other statistical methods to analyze the study data. The study results indicated high levels of strategic thinking, except for deriving hypotheses, as well as high levels of risk management. The levels of practicing organizational support varied between high and medium levels. The results also showed a significant impact of strategic thinking on risk management, in terms of seizing opportunities, systemic perception and deriving hypotheses, while this impact was not significant for strategic intent and thinking in time. In addition, the results indicated a moderating role for organizational support in improving the impact of strategic thinking on risk management. In light of the results, the researchers recommended the managements of Omani contracting companies, in order to raise the levels of strategic thinking, risk management and organizational support and achieve a balance between them, to work on developing the directors’ capacities to look ahead, encourage directors to prepare scenarios and assumptions, use advanced risk control systems and establish a reward system in line with the contributions made by employees.